Role of Social Economic Factors in Promoting Alcoholism in Southern Division Kabale District. - Ainembabazi, Ritah (Kabale University, 2024)
This research report focused on the role of socio-economic factors in promoting alcoholism in the Southern Division of Kabale District. The study utilized qualitative research methods to gain a deeper understanding of the impact of these factors on the community. The research was guided by three main objectives: identifying the causes of alcoholism in the Southern Division, determining the socio-economic factors contributing to alcoholism, and exploring the effects of alcoholism in the area. A sample of 40 participants, including heads and members of the Mothers Union and survivors of domestic violence, was selected through random sampling. Data were collected through in-depth interviews and focus group discussions, and the responses were analyzed using thematic analysis to uncover common themes and patterns. Ethical considerations, such as informed consent, confidentiality, and protecting participants' rights, were carefully adhered to. Although the qualitative approach may limit the generalizability of the findings, it provides a rich, detailed understanding of the complex social issues at hand. The research found that 24% of respondents cited psychological factors as the main reason for alcoholism, while only 10% pointed to marketing and media influence. The study concluded that alcohol consumption in the Southern Division is prevalent, with some individuals starting as early as 8 years old. The availability and affordability of local brews contribute to early alcohol use, especially among young people. Based on these findings, the study recommends that parents and guardians avoid consuming alcohol in the presence of their children and consistently provide guidance and counseling.